Estudo da fadiga em liga de alumínio aeronáutico 7475-T761 - Serrano, Alexandre Costa [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
This work will address the study of fatigue conditions with constant load in an alloy of aluminum analysis 7475 - T761, so we can better understand the conditions of the aircrafts which contain this alloy in their structures. A literature review, which was discussed the concepts of fracture mechanics, fatigue, aeronautical components, chemical analysis of aluminum alloys, fatigue problems that appears in the aircrafts, metallographic analysis, and testing of optical microscopy tensile, fatigue and microhardness, surface analysis (MEV) study of the chemical composition of the alloy in question, the main causes of crashes, was performed, completing the work, analysis of data from tensile test, hardness and fatigue together with the interpretation of images of optical microscopy and scanning electron was taken. The data indicated the high mechanical strength of the alloy, along with its microstructure indicating elongated grains and high surface contour, which shows such resistance by hindering the movement of dislocations. The grooves are clearly shown in the MEV images as well as the classic with increased fatigue loading and subsequent reduction of the number of cycles to rupture behavior shown in the graphs. Therefore we observed the optimal behavior is supported by the league when subjected to fatigue loadings

Este trabalho contempla o estudo sobre condições de fadiga com carregamento constante em uma liga de análise de alumínio 7475 - T761, para que possamos entender melhor as condições em que se encontram as aeronaves que levam tais ligas em suas estruturas. Foi realizada uma revisão bibliográfica, onde foi abordado os conceitos da mecânica da fratura, fadiga, elementos aeronáuticos, análises químicas das ligas de alumínio, problemas que a fadiga proporciona nas aeronaves, análise metalográfica, de microscopia óptica, ensaio de tração, de fadiga e de microdureza, análise de superfície (MEV) e estudo da composição química da liga em questão, as principais causas das falhas, concluindo o trabalho, foi feita a análise dos dados de ensaio de tração, dureza e fadiga em conjunto com a interpretação das imagens da microscopia óptica e de varredura eletrônica. Os dados indicaram a alta resistência mecânica da liga, juntamente com sua microestrutura indicando grãos alongados e alta superfície de contorno, o que evidencia tal resistência por dificultar o movimento das discordâncias. As estrias são mostradas claramente nas imagens do MEV como também o comportamento clássico de fadiga com o aumento da carga e a subsequente diminuição do número de ciclos para a ruptura mostrada nos gráficos. Portanto evidenciamos o ótimo comportamento suportado pela liga quando está submetida a carregamentos de fadiga
Keywords: Resistencia de materiais; Mecânica da fratura; Aluminio - Fadiga; Ligas de aluminio; Engenharia aeroespacial; Strength of materials